2019
DOI: 10.4236/ajac.2019.109029
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Quinine in Pharmaceutical Forms Tablets Find East of the Democratic Republic of Congo

Abstract: The present study focuses on the quality control of quinine in the compressed pharmaceutical forms circulating in eastern Democratic Republic of Congo. The analyses performed on the collected samples included disintegration of the tablets, identification of quinine in the formulations by color reaction methods and thin-layer chromatography. The quantitative analysis was performed by spectrophotometric and volumetric methods. The most significantly observed findings were abnormalities of release; underdosing, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Although a neglected area of research, many of those who have investigated medicine disintegration and dissolution issues, have found evidence of major impairments. In recent surveys in Afghanistan, 58/203 antimalarials failed disintegration tests and in the Democratic Republic of Congo, 5/20 antimalarial quinine tablets failed dissolution tests 35 , 36 . Disintegration tests are often used in screening, such as that available in the portable GPHF-Minilab, but are infrequently followed by laboratory-based dissolution tests.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Although a neglected area of research, many of those who have investigated medicine disintegration and dissolution issues, have found evidence of major impairments. In recent surveys in Afghanistan, 58/203 antimalarials failed disintegration tests and in the Democratic Republic of Congo, 5/20 antimalarial quinine tablets failed dissolution tests 35 , 36 . Disintegration tests are often used in screening, such as that available in the portable GPHF-Minilab, but are infrequently followed by laboratory-based dissolution tests.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The risk of treatment failure due to bad quality is significantly higher with QS tablets than AL fixed-dose products. Studies carried out in Rwanda and the East of DR Congo had also shown the under-dosing and the absence of the quinine [11,45]. One study conducted in DRC [46] According to the WHO, counterfeit AMDs are often sold at low prices because they do not contain the right ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of treatment failure due to bad quality is significantly higher with QS tablets than AL fixed-dose products. Studies carried out in Rwanda and the east of DR Congo had also shown the under-dosing and the absence of the quinine [11,44]. One study conducted in DRC [45] on 150 AL samples collected from private pharmaceutical outlets in 8 main cities (Goma, Kikwit, Kinshasa, Kisangani, Lubumbashi, Matadi, Mbandaka, and Mbuji-Mayi) found 3 (2%) visual inspection failure and 4 (2.7%) TLC test failure.…”
Section: Discussionmentioning
confidence: 99%